2011
DOI: 10.1111/j.1758-0854.2011.01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude and Well‐Being: Who Benefits the Most from a Gratitude Intervention?

Abstract: Background: Theory and research have shown that gratitude interventions have positive outcomes on measures of well-being. Gratitude listing, behavioral expressions, and grateful contemplation are methods of inducing gratitude. While research has examined gratitude listing and behavioral expressions, no study has tested the long-term effects of a gratitude contemplation intervention on well-being. Methods: The present experiment examined the efficacy of a 4-week gratitude contemplation intervention program in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
139
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(157 citation statements)
references
References 41 publications
8
139
1
9
Order By: Relevance
“…This was the only supported hypothesis in the current study. Self-esteem was the only variable to reach statistical significance and add unique variance to the model, supporting prior research which has found a link between self-esteem and gratitude (Emmons and McCullough, 2003;Kashdan et al, 2006;Rash et al, 2011). A post-hoc ANOVA revealed that 5.3% of the variability in gratitude scores can be accounted for by individual's self-esteem levels.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…This was the only supported hypothesis in the current study. Self-esteem was the only variable to reach statistical significance and add unique variance to the model, supporting prior research which has found a link between self-esteem and gratitude (Emmons and McCullough, 2003;Kashdan et al, 2006;Rash et al, 2011). A post-hoc ANOVA revealed that 5.3% of the variability in gratitude scores can be accounted for by individual's self-esteem levels.…”
Section: Discussionsupporting
confidence: 59%
“…This suggests that gratitude may be a self-acceptance-related emotion associated with self-esteem (Rash et al, 2011). A study on Vietnam War veterans found that high levels of gratitude significantly predicted greater self-esteem after controlling for post-traumatic stress severity (Kashdan et al, 2006).…”
Section: Self-esteem In Psychological Healthcarementioning
confidence: 99%
See 3 more Smart Citations